Konstruksi Realitas Pengukuran Tanah di Wadas dalam Media Online Nasional (Analisis Framing Pemberitaan Isu Wadas di Tempo.co Periode 8-11 Februari 2022) - Bayuaji, Bonifatius Wisnumurti; Monggilo, Zainuddin Muda Z. (Universitas Gadjah Mada, 2024)
This research aims to examine the framing of online media coverage by Tempo.co regarding the agrarian land measurement case in Wadas during the period of February 8-11, 2022. The study employs a cognitive paradigm with a qualitative approach. The researchers utilize the Pan and Kosiscki framework model to analyze the media framing in ten online news texts from Tempo.co. In addition to using data from news texts, this research conducts interviews with the Tempo.co editorial team to understand the behind-the-scenes process of news coverage, as well as Tempo.co's framing and values. Through the process of analyzing using the Pan and Kosiscki framing model, Tempo.co exhibits a negative framing of the police actions in Wadas, highlighting police actions that violate human rights principles and emphasizing the conflict's impact on the residents.Insights from the interviews with Tempo.co reveal that the government's indiscriminate labeling of misinformation has a detrimental effect on the media's credibility and undermines the community's struggle to obtain their rights. As an independent media outlet, Tempo.co consistently upholds the standards of accurate, objective journalism that does not harm anyone.